Storyworlds: monty at mcburgers - Bentley, Diana (Heinemann UK, 2009)
Monty, a mischievous raccoon, snuck into McBurgers late at night, hoping for a taste of the secret sauce. He outsmarted the employees, causing chaos in the kitchen, but ended up creating the wildest new burger in the process. The next day, it was the talk of the town$1 (BMonty$1 (Bs Burger became a local legend.s